1987
DOI: 10.1161/01.cir.76.2.469
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of endothelial cell structure and function by intracoronary perfluorochemical in a canine preparation of reperfusion.

Abstract: To determine the effect of intracoronary perfluorochemical on endothelial cell structure and function, 16 dogs were randomized to receive either low-dose (15 ml/kg) intracoronary perfluorochemical (Fluosol-DA) or saline after 90 min of proximal occlusion of the left anterior descending coronary artery (LAD). The animals underwent reperfusion for 60 min with the introduction of perfluorochemical or saline 5 to 10 min after the onset of reperfusion. Endothelium-dependent coronary vasodilatory reserve was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…This result with perflubron emulsion conflicts with our results in the prophylactic group. It has been suggested that PFC may prevent reperfusion injury through anti-inflammatory, effective oxygen-carrying capacities and endothelium preservation [9,24]. The present data suggest that administration of perflubron emulsion improves areas of impaired perfusion when given prior to ischaemia.…”
Section: Area At Risk (% Lv)supporting
confidence: 58%
“…This result with perflubron emulsion conflicts with our results in the prophylactic group. It has been suggested that PFC may prevent reperfusion injury through anti-inflammatory, effective oxygen-carrying capacities and endothelium preservation [9,24]. The present data suggest that administration of perflubron emulsion improves areas of impaired perfusion when given prior to ischaemia.…”
Section: Area At Risk (% Lv)supporting
confidence: 58%
“…Lidocaine was used to prevent cardiac arrhythmias during ischemiareperfusion (Forman et al, 1987). Lidocaine blocks the sodium channels (which accounts for its anti-arrhythmic effect), as well as the ATPsensitive potassium (K ATP ) channels (Barthel et al, 2004).…”
Section: Critique Of Methodsmentioning
confidence: 99%
“…Deflation of the coronary occluder was performed gradually to avoid ventricular fibrillation. A bolus injection of lidocaine (1 mg/kg) (Forman et al, 1987) was administered prior to the CAO to prevent cardiac arrhythmias during ischemia/ reperfusion. The recovery of WT was evaluated for 24 h following reperfusion.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…(Circulation 1991;83:237-247) E a xperimental studies have demonstrated that Reperfusion results in a significant impairment of myocardial salvage after reperfusion may be endothelial-dependent and -independent vasodilalimited by deleterious changes that occur in tory reserve in both large and small vessels after 90 the microvasculature in the perireperfusion period. [1][2][3][4][5][6][7] and 120 minutes of regional ischemia.67 There is extensive disruption of endothelial cells in capillaries of the reperfused bed associated with luminal obstruction by cellular elements, particularly neutrophils.3'5 These abnormalities result in a progressive decrease in blood flow to potentially viable myocytes after reperfusion with eventual lethal injury to these cells (reperfusion injury).113,7,8 Experimental studies support a role for the neutrophil in the pathogenesis of microvascular injury after reperfusion.9-13 Neutrophils may reduce microcirculatory flow by mechanically obstructing capillary lumens'2 or cause extensive endothelial cell disruption through the liberation of cytotoxic substances such as oxygen-derived free radicals and proteolytic enzymes.14-17 Activated neutrophils may further reduce blood flow by the release of vasoactive substances such as leukotrienes and platelet activating factor. '8 Additional limitation of infarct size with neutropenia, anti-inflammatory agents, and antineutrophil agents lend further support to the role of the neutrophil in mediating reperfusion injury.513, '9,20 Adenosine is an endogenous arteriolar vasodilator present in relatively high concentrations at the time of reperfusion.21 It is a metabolic by-product of ATP with numerous properties that may attenuate reperfusion injury, including inhibition of superoxide anion and proteolytic enzyme release by neutrophils,22,23 limitation of endothelial-neutrophil interactions,24 inhibition of platelet aggregation and thromboxane release,25 and augmentation of postreperfusion coronary blood flow.3'7 These cardioprotective efforts of adenosine support the hypothesis that it may be a potentially useful agent in limiting myocardial reperfusion injury.…”
mentioning
confidence: 99%